Prywatne ubezpieczenia zdrowotne w krajach Unii Europejskiej - Pietrzak, Agnieszka (Private Health Insurance in UE, 2005)
The article presents the role of private health insurance in UE countries. In the first section basic information relative to health insurance is introduced. Second part is dedicated to presentation of private health insurance solutions which function in chosen UE member countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 389-400